Social Assistance Rights for Disability in Gresik Distric - Pandu Satriawan Zainulla; Wiwik Afifah (Proceeding International Conference on Religion, Science and Education, 2023)
The fulfillment of the disability group in Gresik Regency, East Java in the social assistance policy (social assistance) who has surrendered to receiving social assistance (social assistance) whose authority lies with the Social Service Office in Gresik Regency. In this research that was conducted in Gresik Regency, it was not only about receiving social assistance to ordinary people, but also paying attention to the policy of accepting social assistance (social assistance) to vulnerable groups of people, one of which is the community with disabilities, where people with disabilities have special needs in their lives. In this case the fulfillment of the policy in receiving social assistance (social assistance) which we held in Gresik Regency in the villages of Gluranploso and Wringinanom we used an empirical juridical research method which had a sociological approach. In this study, it can be found that there are several groups of persons with disabilities in receiving social assistance (social assistance). The disability group in receiving social assistance in the results of this research they received assistance from the Social Service (Dinas Sosial) but from the disability group in fulfilling social assistance (social assistance) in the village of gluran ploso we interviewed there were problems regarding ineligibility in the effort to cause problems that were not liquid as well as rejection of complaints from social assistance (social assistance). And when reporting on this matter, there was no response so that in resolving the problem of the complaint, the disability group was not involved until the disability group was not involved in monitoring and evaluating social assistance (social assistance).